корни произведение корней сумма корней
1) 1;-6; x1x2=-6 x1+x2=-5
2) 12;-2 x1x2=-24 x1+x2=10
3) 7;-8 x1x2=-56 x1+x2=-1
4) 8;-7 x1x2=-56 x1+x2=1
5) 4,192 6;− 1,192 6 x1x2=-5 x1+x2=-3
6) 8;-10 x1x2=-80 x1+x2=-2
7) -3/4;-1 x1x2=3 x1+x2=-7
8) 1;1/5 x1x2=1 x1+x2=6
9) 1,618 ;-0,618 x1x2=-1 x1+x2=1
Пошаговое объяснение:
корни произведение корней сумма корней
1) 1;-6; x1x2=-6 x1+x2=-5
2) 12;-2 x1x2=-24 x1+x2=10
3) 7;-8 x1x2=-56 x1+x2=-1
4) 8;-7 x1x2=-56 x1+x2=1
5) 4,192 6;− 1,192 6 x1x2=-5 x1+x2=-3
6) 8;-10 x1x2=-80 x1+x2=-2
7) -3/4;-1 x1x2=3 x1+x2=-7
8) 1;1/5 x1x2=1 x1+x2=6
9) 1,618 ;-0,618 x1x2=-1 x1+x2=1
Пошаговое объяснение: